Effects of Calf Sex Altering Oral Preparation on Pregnancy Rate and Female Calf Production in the Buffalo - Yadav, Kapil Dev; Pokharel, Aashirbad; Gautam, Gokarna; Shah, Shatrughan; Rekik, Mourad; Pratim, Deka Ram; Varijakshapanicker, Padmakumar; Devkota, Bhuminand (Journal of Buffalo Science, 2026)
Purpose of the Study: The use of calf sex-altering oral preparations (CSAOP) to increase female offspring can offer advantages in field applicability and affordability compared to other sex-manipulation techniques. The current study evaluated the effect of CSAOP (FemEXX®) on pregnancy rate and calf sex ratio in buffaloes. Methods: Parous buffaloes (N = 240) were selected and randomly divided into four groups (60 buffaloes per group). The groups received one of the following treatments: CSAOP alone, CSAOP combined with a special feed supplement, special feed supplement alone, or no treatment (control). At estrus, all buffaloes were bred naturally, and those in the CSAOP alone and CSAOP + special feed supplement groups were orally drenched with 300 mL of FemEXX®, 30 minutes after natural mating. Logistic regression was used to evaluate the effects of treatment and other factors on pregnancy and female calf birth rates, and linear regression was applied for gestation length. Variables significant in univariable analysis were included in multivariable models, with statistical significance set at p< 0.05. Results: The overall pregnancy rate was 76.62%, and no significant difference in pregnancy rate was observed among treatment groups (p = 0.76). However, the proportion of female calves was significantly higher in the CSAOP (78.9%) and CSAOP with special feed (77.1%) groups than in controls (42.5%), with higher odds of female calf birth (OR = 4.64, 95% CI: 1.68-12.78 and OR = 4.22, 95% CI: 1.52-11.72, respectively). Pluriparous buffaloes had higher odds of producing female calves than primiparous animals (OR = 2.18; 95% CI: 1.01-4.70). Gestation length did not differ among treatment groups but was shorter in female-bearing buffaloes (p < 0.01). Conclusion: In conclusion the use of CSAOP is effective in increasing the number of female calves without affecting pregnancy rate in buffaloes.